Pseudotumorcerebri – a rare complication of ATRA based treatment of Acute Promyelocytic Leukaemia (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Acute promyelocytic leukaemia is a highly curable sub type of acute myeloid leukaemia and about 90% of these patients have good chance of survival with current all transretinoic acid based arsenic tri oxide or chemotherapy. However, a rare complication, pseudotumour cerebri may arise following All Trans Retinoic Acid (ATRA) therapy, which may provide obstacle to continue this promising therapy. We present the case report of a young female patient with acute promyelocytic leukaemia treated with Arsenic trioxide (ATO) and ATRA that subsequently develop abrupt onset of lateral rectus palsy and decreased visual acuity due to pseudotumour cerebri. We treated the patient with acetazolamide and kept her at frequent follow up. There was significant improvement of her lateral rectus palsy as well as visual acuity following treatment with acetazolamide that allowed us to continue the primary All Trans Retinoic Acid (ATRA) based treatment.J Bangladesh Coll Phys Surg 2024; 42: 105-108